When the means modify the ends. (E)Valuating and transforming the purpose of a nonprofit organization through impact assessment. - Chantale Mailhot; Valérie Michaud; Sonia Tello-Rozas (Canadian Journal of Nonprofit and Social Economy Research, 2020)
In a context marked by a trend towards marketization and a rise in performance measures, nonprofit organizations (NPOs) suffer pressures to show that their activities have visible impacts. Based on the French pragmatist sociology’s Economies of Worth framework, we explore how NPOs may come to change what they value and what is their fundamental purpose. More specifically, we delve into the process of valuation triggered by the intervention of consultants to help a NPO develop an impact evaluation tool aimed at legitimizing its actions. Our findings show how this process led to a complete redefinition of the NPO’s “theory of change”, ultimately distantiating the NPO from its initial, explicit purposes.